Plasmonic structures fabricated by interference lithography for sensor applications - Menezes, Jacson W.; Nalin, Marcelo [UNESP]; Chillcce, Enver F.; Braga, Edmundo S.; Cescato, Lucila (SPIE, the international society for optics and photonics, 2009)
In this work we demonstrate the use of holographic lithography for generation of large area plasmonic periodic structures. Submicrometric array of holes, with different periods and thickness, were recorded in gold films, in areas of about 1 cm2, with homogeneity similar to that of samples recorded by Focused Ion Beam. In order to check the plasmonic properties, we measured the transmission spectra of the samples. The spectra exhibit the typical surface plasmon resonances (SPR) in the infrared whose position and width present the expected behavior with the period of the array and film thickness. The shift of the peak position with the permittivity of the surrounding medium demonstrates the feasebility of the sample as large area sensors. © 2009 SPIE.
Keywords: Holography; Microfabrication; Plasmonic structures; Surface plasmon resonance; Gold film; Holographic lithography; Interference lithography; Large area sensors; Peak position; Plasmonic properties; Sensor applications; Transmission spectrums; Holographic interferometry; Infrared spectroscopy; Lithography; Microanalysis; Micromachining; Nanostructures; Optical properties; Sensors; Plasmons